Impact evaluation of nutrition sensitive intervention scaled up through preschools - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
In late 2018, the Government of Malawi committed to scaling-up nutrition actions delivered through their ECD platform. With strong global attention focused on how to scale-up multisectoral actions in nutrition leveraging existing platforms, this case study looks at the enabling factors that informed and led to the government’s decision to scale-up nutrition-sensitive actions through Malawi’s ECD platform.